11p15.5 epimutations in children with Wilms tumor and hepatoblastoma detected in peripheral blood. Issue 13 (22nd April 2020) - Fiala, Elise M.; Ortiz, Michael V.; Kennedy, Jennifer A.; Glodzik, Dominik; Fleischut, Megan Harlan; Duffy, Kelly A.; Hathaway, Evan R.; Heaton, Todd; Gerstle, Justin T.; Steinherz, Peter; Shukla, Neerav; McNeer, Nicole; et al.
Abstract : Background: Constitutional or somatic mosaic epimutations are increasingly recognized as a mechanism of gene dysregulation resulting in cancer susceptibility. Beckwith‐Wiedemann syndrome is the cancer predisposition syndrome most commonly associated with epimutation and is extremely variable in its phenotypic presentation, which can include isolated tumors. Because to the authors' knowledge large‐scale germline DNA sequencing studies have not included methylation analysis, the percentage of pediatric cancer predisposition that is due to epimutations is unknown. Methods: Germline methylation testing at the 11p15.5 locus was performed in blood for 24 consecutive patients presenting with hepatoblastoma (3 patients) or Wilms tumor (21 patients). Results: Six individuals with Wilms tumor and 1 patient with hepatoblastoma were found to have low‐level gain of methylation at imprinting control 1, and a child with hepatoblastoma was found to have loss of methylation at imprinting control 2. The loss of methylation at imprinting control 2 was found to be maternally inherited, despite not being associated with any detectable genomic alteration. Conclusions: Overall, 33% of patients (8 of 24 patients) with Wilms tumor or hepatoblastoma were found to have an epigenetic susceptibility that was detectable in the blood. It is interesting to note that low‐level gain of methylation at imprinting control 1 predominantly was detected in females with bilateral Wilms tumors. Further studies in larger cohorts are needed to determine the efficacy of testing all patients with Wilms tumor or hepatoblastoma for 11p15.5 epimutations in the blood as part of DNA analysis because this hallmark of predisposition will not be detected by sequencing‐based approaches and detecting a cancer predisposition may modify treatment. Abstract : In the current study, all patients presenting with Wilms tumor or hepatoblastoma undergo 11p15.5 methylation analysis. Approximately one‐third are found to have an epimutation at this locus that is detectable in peripheral blood.